Multi-senses explication activities module for dyslexic children in Malaysia - Subramaniam, Vijayaletchumy; Mallan, Vijay Kumar; Che Mat, Noor Hayati (Canadian Center of Science and Education, 2013)
Dyslexic children are having abnormal difficulties in reading, spelling and writing. The awareness on these problems leads researcher to conduct a case study in the psycholinguistic field about the multi-senses explication activities in the words mastery among the dyslexic children in Sekolah Kebangsaan Padang Temu Melaka. Starting from the Information Processing Theory by Robert M. Gagne (1975) as the theoretical framework, this research aims to produce a module on the multi-senses explication activities for the dyslexic children in Malaysia. The subjects are five dyslexic children from Sekolah Kebangsaan Padang Temu Melaka. They are in the middle of following through the Dyslexia Specific Learning Problem Integration Programme in that particular school. Data were gathered from Test 1 and Test 2, questionnaire, interview sessions and observations conducted. The findings showed that the multi-senses explication activities could provide the language learning mode, especially on the mastery of the suitable words based on the dyslexic children’s mind. Besides that, researcher also emphasized on the language game element in the students’ learning of the Malay language. The interview sessions and the observations showed the improvised language learning game managed to pull the attention of the students and trigger the fun feelings of the dyslexic children in learning the Malay language which they felt difficult to master previously.